Report on the Piloting of the Quality, Relevance and Comprehensiveness of Impact Mitigation Services Survey (QIMS) in Swaziland - World Bank (Washington, DC, 2013)
The delivery of impact mitigation services has not kept pace with the severity and breadth of HIV related impacts in Swaziland. It has become increasingly clear that the emphasis on short term emergency response initiatives must give way to long-term initiatives to help Swaziland cope with the impacts. As a key step in the roll-out of a more coherent and effective impact mitigation response of greater relevance, the National Emergency Response Council on HIV/AIDS (NERCHA) wants to commission a periodic Quality of Impact Mitigation Survey (QIMS) to measure the quality, relevance, and comprehensiveness of impact mitigation services.